Central African Economic and Monetary Community (CEMAC) : Staff Report on Common Policies and Challenges of Member Countries. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses common policies of the member countries of the Central African Economic and Monetary Community (CEMAC). Medium-term prospects for CEMAC are uncertain. Despite their recent stabilization, oil prices are projected to remain well below pre-shock levels in the medium term. In addition, oil production is projected to start falling after 2017. The Executive Directors have encouraged the authorities to accelerate the reform of the monetary policy framework to improve transmission channels and better manage systemic liquidity. They have also stressed the importance of full compliance with the pooling of foreign exchange earnings with the regional central bank, and called for stepped-up efforts to implement outstanding safeguards recommendations.